STUDI AWAL GRADING BUAH SAWIT DENGAN BANTUAN INJEKSI TEGANGAN LISTRIK SEARAH - Andri Saputra; Wahyu Candra; Yan Soerbakti; Romi Fadli Syahputra; Defrianto Defrianto; Saktioto Saktioto (Universitas Riau, 2019)
Maturity progress of palm fruit is greatly depending on the availability of nutrients and environments. Determining maturity level of palm fruit is important to evaluate the quality of palm oil fruits. The younger or too mature fruits will produce poor quality of crude palm oil (CPO). An appropriate devices are needed that can measure the level of fruit maturity so that uniformity of maturity grade can be carried out to obtain high quality CPO. This research provides a preliminary study of voltage change on the surface of oil palm seeds which subjected by electric potential. The low directional voltage (DC) injection treatment, 10V, was applied to investigate the impact of applied voltage on palm oil seeds with three different levels of maturity, i.e. immature (young), ripe and over ripe . The results shown that oil palm fruit quite quickly responds to injection of DC applied voltage with different responding voltage. This responding voltage tends to increase with increasing maturity levels, but decreases for over ripe fruit which has falling down and starting to dry out.